PANCASILA SEBAGAI SISTEM ETIKA - Sri Rahayu Amri (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
Pancasila and ethics are two things that can not be separated because they both teach about good values. Ethics of Pancasila is an basic ethics about good and bad judgments on the values of Pancasila, namely the value of divinity, human values, the value of unity, the value of democracy and the value of justice. An action is said to be good not only if it is not vulnerable to the values of Pancasila, but how to assign existing values into something more beneficial to others. Referring to the values contained of Pancasila, Pancasila can be a very strong ethical system, the values that exist are not only fundamental, but also realistic and applicable. Values of Pancasila are ideal values that already exist in the ideals of the Indonesian nation that must be realized in the reality of life. Values of Pancasila when fully understood, lived and practiced, certainly able to reduce the level of crime and violations in the life of society, nation and state.Pancasila is a value system that is an organic unity that can not be separated from one another. Thus, it will be a great moral force when the overall value of Pancasila which includes the value of divinity, human values, the value of unity, the value of democracy, and the value of justice are used as moral foundation and applied in all national and state life. The cultivation of values as mentioned above is most effective through education and media. Informal education in the family should be the main foundation and then supported by formal and non-formal schooling in the community. The media must have a vision and mission to educate the nation and to build the character of an advanced society, but still the personality of Indonesia.Keywords : Pancasila, system, Ethics